Characterization of phosphogypsum deposited in Schistos remediated waste site (Piraeus, Greece) - Papageorgiou, F; Godelitsas, A.; Xanthos, S; Voulgaris, N.; Nastos, P.; Mertzimekis, T. J.; Argyraki, A; Katsantonis, G (Uranium - Past and Future Challenges, 2015)
Abstract The operation of a phosphate fertilizer industry in Drapetsona, near Piraeus port (Greece), resulted in the deposition of 10 million tons of phosphogypsum (PG) into an old limestone quarry, in the period 1979-1989. The whole deposit has been recently remediated using geomembranes and thick soil cover with vegetation. The purpose of the present study was to characterize representative samples of that phosphogypsum, using diffraction (powder-XRD), microscopic (SEM-EDS), analytical (ICP-MS), and spectroscopic techniques (High-resolution γ-ray spectrometry and XRF). The material contains crystalline gypsum (CaSO4.2H2O) and Ca-Si-Al-S-F (chukhrovite-type/meniaylovite) phases. The natural radioactivity is mainly due to the $^{238}$U series and particularly $^{226}$Ra (average: 462 Bq/kg), which is relatively low compared to PG from the rest of the world. Furthermore, leaching experiments using local (Attica) rainwater, together with ICP-MS, were performed to assess the potential release of elements in the environment.